Impact of Design Parameters in Thermal Solar Water Storage Tank Systems: (A Review) - Hussain, Narjes; Amori, Karima (Al-Khwarizmi Engineering Journal, 2025)
This work provides a historical overview of water storage tanks used for solar energy collection, with a focus on the impact of different geometric configurations on thermal performance and energy storage efficiency. The designs of cylindrical, spherical, rectangular and triangular tanks were reviewed to analyse their effects on thermal gradients, heat retention and energy storage capacity. Within the scope of nominal processes, the study primarily aimed to identify the factors influencing the choice of tank shape in terms of size, capacity and aspect ratio. Another key objective was to assess what enhances heat storage in the tank to improve thermal efficiency. Comparing cylindrical shapes to other shapes, such as spherical, rectangular, and triangular , it offered the optimal performance with the needed requirements for the objects that have a smaller surface area-to-capacity ratio in addition to the lower heat loss. Furthermore,when the tilt angle with horizontal axes of the storage tank was at 0°, the tanks’ ratio reduction had remarkable impact on thermal stratification . The results might provide valuable information for the thermal storage system’sdesign in solar water heating for improving thermal efficiency. This work provides the basis for research exploiting high-temperature solar energy storage technologies and their applications in building sustainable energy systems.